2010
DOI: 10.2172/989447
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Waste Form Screening Test Results?Cast Stone and Alkali Alumino-Silicate Geopolymer

Abstract: Executive SummaryWashington River Protection Solutions (WRPS) is responsible for the design and construction of upgrades to the Effluent Treatment Facility (ETF) at Hanford necessary to support the 2018 operation of the Hanford Tank Waste Treatment and Immobilization Plant (WTP). Upgrades to ETF will include a Solidification Treatment Unit (STU). The ETF is a Resource Conservation and Recovery Act (RCRA)-permitted multi-waste treatment and storage unit that can accept dangerous, low-level, and mixed wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(68 citation statements)
references
References 14 publications
5
63
0
Order By: Relevance
“…The Cast Stone waste form is the current baseline technology for solidifying the liquid secondary wastes from WTP. Pierce et al, (2010b) demonstrated that the Cast Stone is a viable waste form for immobilization of the WTP secondary wastes. Sundaram et al (2011) conducted additional work to develop and start the optimization of Cast Stone for the secondary liquid wastes to be treated at ETF.…”
Section: Cast Stonementioning
confidence: 99%
See 2 more Smart Citations
“…The Cast Stone waste form is the current baseline technology for solidifying the liquid secondary wastes from WTP. Pierce et al, (2010b) demonstrated that the Cast Stone is a viable waste form for immobilization of the WTP secondary wastes. Sundaram et al (2011) conducted additional work to develop and start the optimization of Cast Stone for the secondary liquid wastes to be treated at ETF.…”
Section: Cast Stonementioning
confidence: 99%
“…The EPA 1313 test method (EPA 2009a) has been used on Cast Stone and DuraLith samples tested during the Phase I investigations of candidate secondary waste forms (Pierce et al, 2010b). Therefore, in this set of tests, EPA 1313 leaching was conducted on only Ceramicrete samples.…”
Section: Epa 1313 Leach Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The projected WTP secondary waste compositions have varied over time as flow sheets and assumptions have changed. More details on the derivation of the WTP secondary waste compositions can be found in the two previous Cast Stone reports (Pierce et al 2010b;Sundaram et al 2011). The compositions of the dissolved species in secondary waste simulants in general are dominated by sodium and hydroxide with significant concentrations of nitrate and oxalate (represents all organic matter) present in many.…”
Section: Range Of Wastes/compositions Testedmentioning
confidence: 99%
“…In 2009, preliminary screening of waste forms was conducted to assess the viability of alternative waste forms for the solidification of the liquid secondary wastes (Pierce et al 2010a;Pierce et al 2010b). A testing program was initiated to further develop, optimize, and characterize the Cast Stone, Ceramicrete, and DuraLith waste forms to stabilize/solidify the anticipated liquid secondary wastes.…”
Section: Introductionmentioning
confidence: 99%